PENERAPAN FAKTOR ERGONOMI GUNA MENINGKATKAN KENYAMANAN DAN KEAMANAN BERAKTIVITAS DI RUMAH TINGGAL - Patradhiani, Rurry; Hastarina, Merisha; Wisudawati, Nidya; Saleh, Zulkifli; Yasmin, Yasmin (Jurnal Abdimas Musi Charitas, 2023)
Human daily activities at home are inseparable from the application of ergonomics. Every activity at home definitely needs a tool to provide support. This program aims to provide education about ergonomic factors that influence daily activities, ergonomic body posture in daily activities at home, and the dangers of doing non-ergonomic activities. Women of Family Welfare Empowerment (PKK) in Ki Merogan area were involved as participants, considering that mothers are family members who do a lot of daily activities at home. In this program, participants were educated about the application ergonomic factors in daily life. People should do activities with an ergonomic body posture in order to create comfort and safety for activities at home. Furthermore, participants were also informed about some of the bad impacts of not applying the ergonomics principles, namely back pain, sprains in the limbs, and even injuries. The counselling session related to ergonomic factors helped participants to know the importance of ergonomics principles and factors in daily life to avoid health problems.